Analysis of the Performance of Regional Government Treasurers in Compiling Reports and Accountability - Tuti Dharmawati; Riska Latifa Alauddin Nur (PT. Banjarese Pacific Indonesia, 2024)
This study aims to analyze the role of local government treasurers in regional financial management, especially in terms of administration and preparation of accountability reports. Based on the importance of accountability and transparency in public financial management, treasurers play a key role in ensuring that regional budget management runs well. This study uses a qualitative method with a literature study approach . review ), where data were obtained from books, journals, laws and regulations, and regional financial reports. The analysis was conducted by exploring various concepts regarding the types of treasurers, their duties and authorities, and the challenges faced in the process of preparing regional financial accountability reports. The results of the study indicate that there are three types of regional government treasurers, namely expenditure treasurers, revenue treasurers, and goods treasurers, each of which has its own duties and roles in managing regional finances. The treasurer's duties include recording, reporting, and accountability for budget use, with great authority in managing regional funds. However, significant challenges are faced in the administration process , such as the complexity of the accounting system and limited competent human resources. In conclusion, to improve the quality of regional financial reports, improvements are needed in the financial information system, increased treasurer competence, and better coordination between treasurers and related agencies. Thus, regional financial management can be more transparent, accountable , and efficient